Alteration of texture and polymorph of phenytoin within thin films and its impact on dissolution. Issue 4 (6th January 2016) - Röthel, Christian; Ehmann, Heike M. A.; Baumgartner, Ramona; Reischl, Daniela; Werzer, Oliver
Abstract : By a change of texture and polymorph the dissolution characteristic of a drug molecule changes. Abstract : Molecular order within a unit cell as well as with respect to a surface in general, has a decisive impact on the dissolution properties of drug molecules. In this work, a model system is investigated; the drug phenytoin (5, 5-diphenylhydantoin) is spin coated onto silica surfaces. Amorphous films results which are then treated at different temperatures. This induces specific orientations (textures) of the unit cell and polymorphic form, thus alterations of organic molecule arrangement with respect to the surface result. Atomic force microscopy measurements reveal extended flat structures at low annealing temperatures (70 °C) while at 90 °C needles start to develop. Spherulites are observed at 100 °C and at 150 °C these spherulites transfer into elongated structures. The morphological differences are also reflected in distinct crystallographic properties as observed by specular X-ray diffraction and grazing incidence X-ray diffraction. A solely 001 texture of the bulk phase is present after annealing at 70 °C while treating at 150 °C results in a 010 texture of the phenytoin crystals. At intermediate temperatures, an additional 012 orientation of the bulk phase is present as well as fractions of a surface mediated phase are evident. Dissolution experiments on the different samples display strong deviations on the drug release into the dissolution media, which is discussed in terms of morphologies and crystalline properties.